PERAN LATIHAN PREHABILITASI PADA OPERASI ELEKTIF TOTAL HIP REPLACEMENT PADA OSTEOARTHRITIS HIP : LITERATUR REVIEW - Rhona Agasti; Dini Nur Alpiah; Zeth Boroh (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2024)
The increasing of elderly population, the prevalence of joint diseases including hip joints, and the need for a holistic approach to patient care have become major concerns in the development of prehabilitation exercise strategies that can be effectively applied. The length of stay, functional abilities, daily living activities, and post-total hip replacement (THR) quality of life are areas that need continuous improvement. This research aims to analyze the impact of prehabilitation exercises on post-operative outcomes in patients undergoing total hip replacement for hip osteoarthritis. A literature review study was conducted using PICO and MeSH search strategies in four databases, namely ProQuest, ScienceDirect, EMBASE, and MEDLINE. The screening process was performed according to criteria, and critical appraisal was conducted using a checklist. The literature search yielded a total of 20 articles meeting the criteria, indicating an impact on functional capacity in 12 articles and no impact in 4 articles. The length of hospital stay was discussed in 6 articles with the results of 3 significant articles and 3 insignificant articles. The most recommended type of exercise was strengthening/resistance exercise combined with endurance training. Although there is no guideline for prehabilitation exercises, it is recommended to perform exercises at least twice a week for a minimum of six weeks before surgery. Analysis indicates that prehabilitation exercises, especially strengthening and endurance exercises, are effective in improving functional capacity.